Factors that contribute to a successful nursing student's decision to withdraw from a bachelor of science in nursing program before graduation. - Randall, Shelly (Factors That Contribute to a Successful Nursing Student's Decision to Withdraw From a Bachelor of Science in Nursing Program Before Graduation, 2013)
There is an extreme shortage of registered nurses (RNs) in the United States (U.S.). This shortage is projected to grow to 260,000 RNs by the year 2025 (American Association of Colleges Nursing [AACN], 2010a). In order to meet the current and future health care needs of the population of the U.S., nursing schools would have to graduate at least 30,000 registered nurses annually. According to the AACN, this calls for a 30% increase in the current number of nursing students graduating from Bachelor of Science in Nursing (BSN) programs (2010a). The purpose of this qualitative study was to discover the reasons that successful nursing students voluntarily left a BSN program at a mid-sized southern university in the U.S. The specific aims of the study were to: (1) determine the factors that influenced successful nursing students' decisions to voluntarily leave this nursing program, and (2) propose evidence-based strategies for retaining successful nursing students in this educational setting. Action Research served as the methodology for this study within the philosophical framework of Heideggerian hermeneutic phenomenology. Hermeneutic phenomenology was used to analyze and interpret the data collected from the participants using Diekelman's (1989) seven step data analysis method. Data were collected via semi-structured interviews and a demographic survey. Rigor was demonstrated using trustworthiness and authenticity criteria. The findings of this study showed that the attrition of successful nursing students was related to a change in the participant's view of nursing, their personal circumstances, or views of themselves. This change revealed the constitutive pattern Nursing was not right for me as the overarching reason the participants in the study left their nursing programs. The themes Internal struggle for a nursing career and Realties of nursing and the seven related subthemes illuminate the lived experiences of these participants that ultimately contributed to their premature departure from their nursing programs.